A Plea for Old Cap Collier - Cobb, Irvin S. (Irvin Shrewsbury), 1876-1944 (Salt Lake City, UT : Project Gutenberg, 1999)
"A Plea for Old Cap Collier" by Irvin S. Cobb is a reflective piece that combines personal anecdotes and societal commentary written in the early 20th century. The book serves as a nostalgic homage to the "nickul libruries" or dime novels of the author's youth, which he argues provided thrills and moral lessons that were lacking in more conventional literature of his time. Cobb critiques the literary and moral values imposed by formal education, promoting a defense of the adventure stories he loved. In this essay, Cobb revisits his childhood experiences with literature, particularly how dime novels like the "Old Cap Collier" series shaped his imagination and values. He laments educational literature's excessive moralistic tone and lack of action, comparing the exciting narratives of dime novels to the often tedious and unrealistic tales found in school readers. Through a humorous and engaging style, he advocates for the richness and importance of these adventure tales, suggesting that they fostered a sense of justice and adventure in young readers, in stark contrast to their more staid educational counterparts. Ultimately, Cobb's work underscores the value of embracing stories that inspire and excite, rather than those that simply adhere to rigid moral structures. (This is an automatically generated summary.)
Release date is 1999-09-01
Produced by Kirk Pearson, and David Widger
Keywords: American wit and humor; Children's literature -- History and criticism; Dime novels -- History and criticism